Is there an association between inflammatory markers and lower physical performance in older adults? - Betty Manrique-Espinoza; Rosa Palazuelos-González; Victoria Pando-Robles; Oscar Rosas-Carrasco; Aarón Salinas-Rodríguez (BMC Geriatrics, 2022)
Abstract Background Maintenance of physical performance is essential for achievement of healthy aging. A few studies have explored the association between inflammatory markers and physical performance in older adults with inconclusive results. Our aim was to analyze the association of tumor necrosis factor-alpha (TNF-α), Interleukin-10 (IL-10), and C-reactive protein (CRP) with physical performance in a sample of older adults in rural settings of Mexico. Methods Our study comprised 307 community-dwelling older men and women who participated in the third wave of the Rural Frailty Study. We assessed the physical performance with the Short Physical Performance Battery (SPPB) and classified older adults as low performance if SPPB scored ≤8. Inflammatory markers were ascertained using serum by immunodetection methods. Logistic regression models were used to estimate the associations between inflammatory markers and physical performance. Results In comparison with the normal physical performance group, low physical performance individuals mainly were female (P <  0.01), older (P <  0.01), more illiterate (P = 0.02), more hypertensive (P < 0.01), fewer smokers (P = 0.02), and had higher CRP levels (P < 0.01). The logistic model results showed a significant association between the 3rd tertile of CRP and low physical performance (OR = 2.23; P = 0.03). IL-10 and TNF-α levels did not show a significant association. Conclusions The results of this study were mixed, with a significant association of physical performance with higher CRP levels but nonsignificant with IL-10 and TNF-α. Further studies with improved designs are needed by incorporating a broader set of inflammatory markers.